1982
DOI: 10.1002/ijc.2910290406
|View full text |Cite
|
Sign up to set email alerts
|

Final case reporting from the ugandan prospective study of the relationship between ebv and burktit's lymphoma

Abstract: A prospective epidemiological study was carried out in the West Nile District of Uganda from 1972 to 1979 in order to investigate the aetiological role of the Epstein-Barr virus (EBV) in Burkitt's lymphoma (BL). By 1976, fourteen BL cases had been detected among the 42,000 children originally bled in the study area. Testing of sera from BL candidates and neighbourhood controls showed that children who develop BL later have EBV/VCA titres several dilutions higher than their age- and sex-matched neighbours. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
2

Year Published

1983
1983
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 7 publications
6
59
0
2
Order By: Relevance
“…The reasons for this finding may not be unconnected with the poor control of infections by Epstein Barr virus (EBV) and plasmodium falciparum (malaria parasite), which are the two infections strongly associated with the pathogenesis of Burkitt's lymphoma. 19,20 However, it was reported that funding to control malaria in sub-Saharan Africa has increased between 1999 and 2004. 21 Apart from controlling repeated attacks of malaria, the molecular genetics of Burkitt's lymphoma need to be revisited.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this finding may not be unconnected with the poor control of infections by Epstein Barr virus (EBV) and plasmodium falciparum (malaria parasite), which are the two infections strongly associated with the pathogenesis of Burkitt's lymphoma. 19,20 However, it was reported that funding to control malaria in sub-Saharan Africa has increased between 1999 and 2004. 21 Apart from controlling repeated attacks of malaria, the molecular genetics of Burkitt's lymphoma need to be revisited.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by seroprofiling studies, which demonstrate that elevated antibody titers to viral capsid antigen (VCA) and the Z Epstein-Barr replication activator (ZEBRA) protein are associated with holoendemic malaria exposure (49). An elevation in these antibody titers signifies viral reactivation (50), and higher VCA antibody titers were observed prior to the development of eBL in a study of Ugandan children (51,52). In addition, malaria infection in concert with EBV reactivation may modulate elements of the innate immune system that influence T-cell maturation and differentiation (53,54).…”
Section: Interestingly Cd8mentioning
confidence: 97%
“…EBV lytic infection in vivo has been identified by elevated antibody titers against EBV lytic antigens and by increased viral DNA load in the serum/plasma, and these observations correspond with advanced cancer stages, poor prognosis or tumor recurrence following therapy (9,10). Additionally, serological studies have indicated that EBV lytic infection may occur months or years prior to a clinical diagnosis of NPC, HD or Burkitt's lymphoma, which suggests EBV lytic infection may be a risk factor for cancer development (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%